Arthropod autophagy molecules facilitate Anaplasma phagocytophilum infection of Ixodes scapularis tick cells - Jeremy W. Turck; Hameeda Sultana; Girish Neelakanta (Communications Biology)
Abstract Ixodes scapularis ticks transmit several medically important pathogens including Anaplasma phagocytophilum to humans and animals. In this study, we provide evidence that A. phagocytophilum modulates autophagy molecules for its survival in tick cells. qRT-PCR analysis revealed that A. phagocytophilum infection results in the upregulation of tyrosine phosphatase, shp-2, and serine/threonine-protein kinase, mTOR, in ticks and tick cells. RNAi-mediated knockdown of shp-2 or functional blocking with SHP-2 inhibitor resulted in significantly increased bacterial burden and reduced phospho-mTOR levels in A. phagocytophilum-infected tick cells. In addition, treatment of A. phagocytophilum-infected tick cells with rapamycin (mTOR inhibitor) resulted in significantly increased bacterial burden and reduced phospho-mTOR levels. Furthermore, expression of autophagy molecules such as atg14 and ulk1 were noted to be upregulated in both A. phagocytophilum-infected unfed ticks and tick cells. RNAi-mediated silencing of atg14 or ulk1 affected bacterial growth in tick cells. Collectively, these results not only indicate distinct host and pathogen responses in tick-A. phagocytophilum interactions but also suggest that this bacterium modulates autophagy molecules for its survival in ticks.